Hybrid PI-MPC Control System for a Four-Phase Interleaved Boost Converter: Performance Evaluation in Reducing Current Ripple in Electric Car Battery Charging - Ikawanty, Beauty Anggraheny; Safitri, Hari Kurnia; Fauziyah, Mila; Irawan, Bambang; Taufik, Taufik; Risdhayanti, Anindya Dwi (Association for Scientific Computing Electronics and Engineering (ASCEE), 2025)
Electric car batteries face two primary challenges: the substantial number of batteries used, leading to increased weight and costs, and the limited battery lifespan, which results in high maintenance expenses. To address these issues, a power supply with high voltage gain and optimal efficiency is essential. Currently, switching mode power supplies are preferred due to their superior efficiency over linear systems. Among these, DC-DC boost converters are key components. However, conventional boost converters face limitations such as restricted voltage gain and significant current ripple, which negatively affect battery performance and system efficiency. This study aims to design a hybrid control system for a four-phase interleaved boost converter, integrating Model Predictive Control (MPC) with Proportional-Integral (PI) control. The hybrid control system dynamically adjusts the PI controller's setpoint based on real-time input variations, enhancing the system’s responsiveness and stability under fluctuating load and voltage conditions. The experimental setup includes a four-phase interleaved boost converter with split inductance and capacitance bypass techniques to mitigate ripple effects. Our hypothesis posits that the hybrid PI-MPC control system will reduce current ripple and improve system performance in electric vehicle battery applications. Results show a significant reduction in input current ripple (0.0014%) and output current ripple (0.042%), indicating improved performance compared to conventional converters. Despite these improvements, the study acknowledges limitations related to the scalability of the proposed system and potential challenges in integrating this topology into larger systems. Further investigation is required to assess its long-term performance and economic feasibility in diverse EV applications.